Solve (e^(x^2))` , use this result to solve §5x*e^(x^2)dx
* is multiply
` is derive
3.§a^xdx=1/ina*a^x+C (a is a number)
The Attempt at a Solution
(I'm alittle confused as to how you 'use' the previous one to solve the next.
The previous example simply states this when solving: [in((x^2)+4)]`
[in((x^2)+4)]`= (in u)`= (1/u)*u`= 1/((x^2)+4)*2x=(2x)/((x^2)+4)
Then you're going to use this to solve §(3x)/((x^2)+4)dx
gives: §(3x)/((x^2)+4)dx = 3/2§(2x)/((x^2)+4)dx= 3/2*in((x^2)+4)+C.
It's not written, so I suppose they are using it by simply putting 3/2 on the outside, using rule 4)
So my try went:
(e^(x^2))`=(e`u)`*u`(um, using the corerule as it is named in norwegian) = e^(x^2)*2x
, which was correct.
Then you use it..
§5x*e^(x^2)dx=(ADSFSDF PRESSING SHIFT FOR A LONG TIME CAN*T WRITE LOL F:: WINDOWS LOL)